Challenges to national unity in Somalia: in-depth investigation from post-2012 to 2022 - Omar Arabow Addan (Cogent Social Sciences)
This study investigates the challenges to national unity in Somalia between 2012 and 2022. Guided by four key objectives, it examines external influences, domestic social factors, economic disparities, and political-institutional weaknesses affecting national cohesion. Using a phenomenological qualitative approach, data were collected from 21 respondents, including political, clan, and religious leaders who play pivotal roles in Somalia’s governance. Findings reveal that the interests of international and regional actors have contributed to national fragmentation. Domestically, the clan-based social structure has fostered political and economic exclusion, intensifying inter-communal tensions. Economic inequalities, particularly in the ownership and control of resources, were seen to favor a small elite, deepening perceptions of marginalization. Furthermore, weak political institutions and an ineffective legal framework have undermined unity efforts. The study concludes that national unity in Somalia requires a more equitable distribution of resources, ensuring inclusive access to public services across clans. It also emphasizes the importance of fostering inclusive political dialogue and strengthening institutions to combat extremism while respecting Somalia’s religious and cultural identity. Addressing these multifaceted challenges is essential for rebuilding a cohesive and stable Somali nation.